(3OQGSI JMdjdjI dJbhje YfGUQ GddjGbI GdHOfjI h YdGbJgG HGdJMUjd GdOQGSj aj GdWhQ GdKGfhj (B: (3OQGSI ejOfjI Jef HeJhSWGJ HdOjI Badh hdGjI GdGZhGW s - (3aJM Gddg , YRhRs; (3HhNQGR, QVhGfs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2021)
(3JfGhdJ GdOQGSI GdYdGbI GdGQJHGWjI Hjf eSJhi GddjGbI GdHOfjI hGdJMUjd GdOQGSj dOi GdJdejP aj WhQ GdeJhSW hgPG dEHQGR CgejI GdfTGW GdHOfj aj JfejI hGdMaGX Ydi GdUMI GdHOfjI hGdfaSjI eeG jLYd GdJdejP CcKQ GSJYOGO ddJYde(B. (3Je GSJNOGe GdefgL GdhUaj GdJMdjdj ef NdGd LeY GdHjGfGJ dGNJHGQGJ ejOGfjI dbjGS GddjGbI GdHOfjI (B((3GdLQj GdSQjY (B50(3e , GNJHGQ ejfj chHQ, GdeVNI, GNJHGQ SGQLfJ, GdLQj GdeQJO, hGdGfMfGA ef Gdhbha(B)(3, GdYjfI HdZJ (B250 (3JdejP ef GdLfSjf Je GNJjGQge Ydi CSGS GdfJGFL GdOQGSjI (B((3eeJGR, LjO, eJhSW, VYja, VYja LOG(B)(3, Je JMdjd GdeYWjGJ GMUGFjG ef NdGd HQfGeL (B19 spss. (3GdfJGFL HjfJ Cf gfGc YdGbI GQJHGWjI GjLGHjI bhjI Hjf eSJhi GddjGbI GdHOfjI heSJhi GdJMUjd GdOQGSj(B.s
(3OcJhQGgs
Keywords: (3GdJMUjd GdOQGSjs; (3GddjGbI GdHOfjIs; (3fTGW HOfj QjGVj JQHhjs